Longitudinal Evaluation of Humoral Immunity and Bacterial and Clinical Parameters Reveals That Antigen-Specific Antibodies Suppress Inflammatory Responses in Active Tuberculosis Patients - Mamiko Niki; Takashi Yoshiyama; Yuji Miyamoto; Masao Okumura; Makoto Niki; Ken-ichi Oinuma; Yukihiro Kaneko; Sohkichi Matsumoto; Yuka Sasaki; Hideo Ogata; Hajime Goto; Shoji Kudoh; et al. (Journal of Immunology Research)
A novel tuberculosis vaccine to replace BCG has long been desired. However, recent vaccine trials focused on cell-mediated immunity have failed to produce promising results. It is worth noting that most commercially available successful vaccines rely on humoral immunity. To establish a basic understanding of humoral immunity against tuberculosis, we analyzed and evaluated longitudinal levels and avidity of immunoglobulin to various tuberculosis antigens compared with bacterial and clinical parameters during treatment. We found that levels of IgG antibodies against HrpA and HBHA prior to treatment exhibited a positive correlation with bacterial burden. Analysis of changes in CRP during treatment revealed an association with high levels of specific IgG and IgA antibodies against mycobacterial antigens. Levels of CRP prior to treatment were negatively associated with IgG avidity to CFP-10 and MDP1 and IgA avidity to HrpA, while IgA avidity to MDP1 and Acr exhibited a negative correlation with CRP levels after 60 days of treatment. These results may provide insight for the development of a novel tuberculosis (TB) vaccine candidate to induce protective humoral immunity against tuberculosis.